The embodiment of the ecological concept and climatic adaptability in the spatial structure of the traditional chinese dwelling with a courtyard - Zhang Yimeng; Korotich Andrey V. (Архитектон, 2023)
The article analyzes the logic and distinctive features of the structural construction of traditional Chinese dwellings with a courtyard. A detailed comparison of various types of such dwellings located in different geographical and climatic regions of China allows us to identify their compositional features and unique architectural solutions. The focus of the study is on the ecological principles and strategies of climatic adaptation of various compositional types of courtyards that allowed them to effectively cope with climatic challenges over centuries. Attention is drawn to the basic philosophical concept of harmonious coexistence of man with nature, which underlies the design of optimal types of traditional Chinese dwellings, particularly to passive methods of architectural design that contribute to environmental sustainability and climatic adaptation of these dwellings.